Hérnia perineal em cães - Mortari, Ana Carolina [UNESP] (2005)
The perineal hernia occurs more frequently in middle aged to aged male dogs, sexually intact, and it may be unilateral or bilateral. Because this disease may have high rate of recurrence and postoperative complications, the aim of this paper is to describe the clinical signs, diagnosis, foccusing to surgical treatments. Among the most effective techniques of pelvic diaphragm reconstruction are the single or associated muscular transpositions, such as internal obturator muscle transposition or superficial gluteal muscle transposition. In cases of recurrences, complementary methods such as colopexy and cystopexy by deferent duct fixation, or more complex procedures as semitendinosus muscle transposition may be used.